Effects of precipitation variation and trampling disturbance on seedling emergence of annual plants in a semi-arid grassland - Liu, Xinping; He, Yuhui; Cheng, Li; Hu, Hongjiao; Xu, Yuanzhi (Frontiers in Environmental Science, 2023)
Precipitation change and grazing are the main factors influencing vegetation structure and dynamics in semi-arid grassland. However, the effects of precipitation variation and livestock trampling on the seedling emergence patterns of plants remain largely unknown. In this study, an experiment with four gradients of trampling (no-trampling, light, moderate, and heavy) and three precipitation treatments (ambient precipitation, +30% precipitation, and –30% precipitation) was conducted to assess the effects of trampling disturbance and precipitation variation on seedling emergence of annual plants. The results showed that an increase in precipitation significantly improved total seedling emergence by 3.5–3.6 times and seedling density of grasses by more than 4.1 times under trampling conditions, while significantly improving total seedling emergence and density of forbs under no-trampling conditions. Moreover, +30% precipitation significantly improved the seedling proportion of grasses under light, moderate, and heavy trampling, while decreasing the seedling proportion of forbs. Seedling emergence of forbs was more sensitive to trampling disturbance, and seedling emergence of grasses was more sensitive to precipitation changes, especially under trampling conditions. Light and moderate trampling with a +30% precipitation increase promoted seedling emergence of grasses, and no trampling with a +30% precipitation increase improved seedling emergence of forbs. Thus, targeted grazing management measures should be implemented for plant communities dominated by either grasses or forbs under changing precipitation conditions.